Kematian yang Ditolak di Kampung Pitu, Nglanggeran, Patuk, Gunungkidul - Nuraini Sekarsih, Fitria (DEMOS: Journal of Demography, Ethnography and Social Transformation, 2022)
This research was conducted in Kampong Pitu, Kapanewon Patuk, Gunungkidul Regency. In accordance with the toponym Pitu which means seven, this kampong has a unique tradition related to historical origins, the number of families who have to live in this village, and of course funeral traditions that are still firmly held by local residents. This research uses in-depth interviews with local leaders of Kampong Pitu, Family Heads, Local Youth, and Nglanggeran Pokdarwis related to the traditions of who can use water and land resources from generation to generation, who can stay, various kinds of reinforcements that occur to residents who trying to break the traditions in this village, and finally the study of death in this location. This death study consists of two things, namely the beliefs of residents for those who violate customary rules and who may be buried in Kampong Pitu.